Enhancing phosphorus availability and dynamics in acidic soils through Rice straw biochar application: a sustainable alternative to chemical fertilizers - Wei He; Wei He; Wei He; Jun Zhang; Jun Zhang; Weichun Gao; Weichun Gao; Yifei Chen; Yifei Chen; Zheng Wei; Zheng Wei (Frontiers in Sustainable Food Systems)
Phosphorus is a vital nutrient for crop growth, but its bioavailability is often limited in acidic soils, which are prevalent in many agricultural regions, including South China. These soils are characterized by low phosphorus availability and high levels of phosphorus fixation, which exacerbate the need for sustainable agricultural practices. Over-reliance on phosphate fertilizers has led to environmental concerns, such as phosphorus accumulation and eutrophication. This study investigates the potential of straw biochar to improve phosphorus dynamics in two typical South Chinese soils: high-phosphorus paddy soil and low-phosphorus lateritic red soil. Using a range of biochar application rates, we examined the effects on phosphorus fractions, phosphatase activity, and microbial biomass phosphorus. The results indicate that biochar significantly increased phosphorus availability, enhanced soil enzyme activity, and boosted microbial phosphorus content, especially in the phosphorus-deficient red soil. These findings underscore the potential of biochar as a sustainable solution for enhancing phosphorus management, improving soil fertility, and reducing environmental risks in South China and similar regions. This research contributes valuable insights into biochar’s practical applications in sustainable agriculture, offering a promising approach to improve phosphorus use efficiency and soil health.